TAPEWORMS (CESTODA: OPHIOTAENIA) FROM THE NORTHERN COTTONMOUTH (AGKISTRODON PISCIVORUS) - Scholz, Tomáš; de Chambrier, Alain; McAllister, Chris T; Tkach, Vasyl V; Kuchta, Roman (The Journal of parasitology, 2023)
The northern cottonmouth, Agkistrodon piscivorus (Lacépède, 1789) (Viperidae: Crotalinae), occurs in the southeastern United States and is one of the few semiaquatic vipers in the world. Three proteocephalid tapeworms of the genus OphiotaeniaLa Rue, 1911 (Cestoda), have been described from this venomous snake. A critical evaluation of type specimens and tapeworms recently collected from A. piscivorus has revealed that only 2 species, Ophiotaenia marenzelleri (Barrois, 1898) and Ophiotaenia grandisLa Rue, 1911 (new synonym Ophiotaenia agkistrodontis [Harwood, 1933]), are specific parasites of this crotaline viper; both species are redescribed here. Ophiotaenia grandis was originally described from a mixture of 2 species: 'true' O. grandis, which is indistinguishable from O. agkistrodontis described 22 yr later and thus considered to be a junior synonym of O. grandis, and O. marenzelleri. Ophiotaenia marenzelleri, also reported from the pygmy rattlesnake, Sistrurus miliarius (Linnaeus, 1766), is a larger tapeworm with a massive scolex, a large cirrus sac, a very large, annular vaginal sphincter near the equatorial gonopore, and an oval, 3-layered embryophore surrounded by a nearly square hyaline outer membrane. Ophiotaenia grandis is much smaller and more slender and has a narrower scolex, a smaller cirrus sac and vaginal sphincter, a 2-layered embryophore, and a distinctly pre-equatorial gonopore. In addition to O. marenzelleri and O. grandis, other Ophiotaenia species typical of semiaquatic snakes (Colubridae: Natricinae) may be present in the northern cottonmouth, which serves only as a postcyclic or occasional host. There is also a tabular summary of 18 species of Ophiotaenia from semiaquatic snakes worldwide, with information on their hosts, distribution, and taxonomically important characters, including key measurements.
Keywords: Peritoneal Cavity; Cestoda; ženské pohlaví; zvířata; Female; Agkistrodon; peritoneální dutina; jihovýchod USA; Southeastern United States; Animals